Graphene Aerogel-Based Flexible Pressure Sensor for Physiological Signal Detection and Human–Machine Interaction - Wang, Zihan; Zhao, Zeshang; Tu, Qiyang; Yao, Chengpeng; Liu, Zhao; Zhou, Chengzhi; Xu, Luxiang; Guo, Shijie; Meng, Chuizhou; Shao, Gaofeng; Cheng, Huanyu; Yang, Li (Nano-Micro Letters, 2026)
Despite extensive development of flexible pressure sensors, it is still difficult for them to simultaneously achieve high precision and a large response to subtle pressures. To address these challenges, this work demonstrates a flexible pressure sensing platform that features the reduced graphene oxide aerogel sandwiched between a polydimethylsiloxane encapsulation layer and a thin polyimide film with interdigital electrodes. The resulting pressure sensor exhibits a high sensitivity of 698.96 kPa−1 and a low limit of detection ( 1 Pa), and outstanding stability over 20,000 loading/unloading cycles. Besides monitoring various physiological signals and human motions, the flexible pressure sensors can be configured into an array layout as a smart artificial electronic skin to recognize the spatial pressure distribution. The flexible pressure sensor can also be integrated with signal processing and wireless communication modules as a teleoperation system for gesture recognition, force feedback control, and kitchen food recognition, highlighting future potential toward smart robotics and human–machine interfaces. Highlights: 1 Reduced graphene oxide aerogel (rGOA) was prepared via freeze-casting, featuring an ultra-light density (10 mg cm−3) and a unique anisotropic structure, which bring advantages to pressure sensing. 2 The rGOA-based pressure sensor exhibits a sensitivity as high as 698.96 kPa−1, a detection range as wide as 100 kPa, and a cyclic stability of over 20,000 cycles. 3 The integration of rGOA with manipulators enables teleoperation, stable grasping of fragile objects with force-feedback and 100% accuracy in food recognition.